RANCANG BANGUN SISTEM PENILAIAN KINERJA GURU DAN TENAGA KEPENDIDIKAN BERBASIS KPI UNTUK MENINGKATKAN PELAYANAN SEKOLAH - Arief Saptono; Siti Hajar; Citha Pardiani Atmaja Putri (UNIVERSITAS RAHARJA, 2020)
The process of evaluating the performance of teachers and education personnel in several schools is still carried out manually, where the calculation of performance is only seen based on absenteeism and is still very subjective, this is quite time consuming in the calculation so thatit is ineffective and inefficient besides the results are less accurate. To overcome the problems above, we need a computerized system so that it can solve the problem and speed up the process. Therefore, this study proposes the design of teacher and staff performance appraisal systems automatically based on data collection methods, pieces analysis to evaluate system performance, and design methods using uml (unifield modeling language) which includes usecase, activity, squence and class diagrams as a tool to provide an overview of the design that is running or will be created. Then for the database processing using mysql, which will ultimately produce a well-integrated system, so that the model created is expected to be able to calculate the performance of teachers and education personnel quickly, accurately, objectively and transparently. This can be done because the calculation process is computerized, and the assessment categories include very good, good, sufficient and less. In addition the existence of a dashboard in the form of recapitulation can be used as a basis for decision making.